Institutionalization of Rural Sanitation Capacity Building in Indonesia - World Bank (Washington, DC, 2015)
Indonesia has made significant increase in rural sanitation access and services from 20.64 percent in 2006 to 44.09 percent in 2013. A study conducted in 2012 estimated a capacity gap of 12,000-18,000 sanitation professionals (from engineers to community workers) to meet the 2015 millennium development goal (MDG) targets, with 30 percent of community health centers not having frontline sanitation personnel. Capacity building programs have so far been largely conducted by technical units, projects, and local government offices. Following an assessment on how and where to best address the issues, the technical assistance (TA) recommended a transformative approach, away from project-based cascading training where training is done at national level and then repeated and cascaded to provincial, district, sub-district, and village levels to an institutionalized capacity building program. The institutionalization of capacity building program targeted two primary audiences: future professionals (pre-service) addressed through integrating national strategy for community-based total sanitation (STBM) modules into health polytechnic schools curriculae and current professionals (inservice) addressed through accredited and certified training programs, with an additional e-learning scheme to reach out to a wider group of professionals and interested parties. The support to scale-up the use of the STBM human resource capacity building system can be provided via a circular letter of Ministry of Health (MoH) to local health offices and STBM partners. Continuous support through the MoH system to follow-up and evaluate outcomes of training and education will be key to sustainability and roll-out across all provinces of Indonesia.